Analysis of Factors Affecting the Low Use of Vasectomy Family Planning (KB) in Rantau Selatan District, Labuhanbatu Regency - Norisa Rambe; Heru Santosa; Asfriyati Asfriyati; Ahmad Budiman Siregar (Budapest International Research and Critics University, 2022)
The purpose of this study was analysis of factors affecting the low use of vasectomy family planning (KB) in Rantau Selatan District, Labuhanbatu Regency. This study uses qualitative research methods with phenomenological approach. Informants were taken using purposive sampling technique. Data collection methods consist of primary, secondary, and tertiary data. The data analysis technique used in this research is qualitative analysis. The results showed that the factors affecting the low use of vasectomy KB were knowledge, rumors/myths in society, culture, husband's attitude, religion, gender, and wife's support.